Effect of hip flexion angle on stiffness of the adductor longus muscle during isometric hip flexion. (February 2021) - Kato, Takuya; Taniguchi, Keigo; Kikukawa, Daisuke; Kodesho, Taiki; Katayose, Masaki
Abstract: This study examined the effect of hip flexion angle on the stiffness of the adductor longus (AL) muscle during isometric hip flexion. Seventeen men were recruited. Ten participants performed submaximal voluntary contraction at 0%, 25%, 50%, and 75% of maximal voluntary contraction (MVC) during isometric hip flexion after performing MVC at 0°, 40°, and 80° of hip flexion. Seven participants performed submaximal voluntary tasks during isometric hip extension in addition to hip flexion task. The shear modulus of the AL muscle was used as the index of muscle stiffness, and was measured using ultrasound shear-wave elastography during the tasks at each contraction intensity for each hip flexion angle. During hip flexion, the shear modulus of the AL muscle was higher at 0° than at 40° and 80° of hip flexion at each contraction intensity ( p < 0.016). Conversely, a significant effect was not found among hip flexion angle during hip extension at 75% of MVC ( p = 0.867). These results suggest that mechanical stress of the AL muscle may be higher at 0° of hip flexion during isometric hip flexion.